The Use of Twisting and Tightening Tool to Strengthen the Cerclage and Tension Band Wiring. (February 2021) - Uygur, Esat; Yayla, Mehmet A.; Yürektürk, Yakup; Akpinar, Fuat
Cerclage and tension band wiring are being used in most bone surgeries in different disciplines. The regularity of the twist on the node of a cerclage and tension band is thought to determine cerclage stability. For this purpose, a novel twisting and tightening tool was designed. This tool maintains extremely regular twists on the node, which we consider to be important for stability. In the present biomechanical trial, we aimed to investigate the consistency of the twists forming the cerclage node. This study was performed on a total of 30 cerclage loops. In group A (n = 15), the cerclage wire was tightened manually by a clipper, while in group B (n = 15), it was tightened using the twisting and tightening tool. In biomechanical tests, the cerclage loops were pulled apart by 2 hooks connected to the biomechanical device. The velocity was adjusted to 20 mm/min. On statistical analysis, there was a significant difference in the ultimate strength ( P = .03) and the mean tensile strength ( P = .01) between groups A and B. It was found that the strength of the cerclage wire can be increased by maintaining more regular twists. The twisting and tightening tool is a reasonable and useful device for both clinical and experimental usages.